(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
In the metallurgical industry, it is of great importance to improve the quality of steel in the process of thermal treatment of structural and tool steels for the field of tool making. In the process of heat treatment, coolants are used in traditional ways. According to the results of our experience, it was found that in the development of the technological process of increasing the physical-mechanical, technological properties of materials under the influence of a magnetic field under different conditions of cooling fluids, it is possible to achieve high strength under the influence of a magnetic field to thermal treatment fluids of steel 45.